2020
DOI: 10.1002/cbin.11482
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mesenchymal stem cells inhibit cardiac hypertrophy by enhancing FoxO1 transcription

Abstract: Bone marrow–derived mesenchymal stem cells (BMSCs) have therapeutic potential for certain heart diseases. Previous studies have shown that stem cells inhibit cardiac hypertrophy; however, it is necessary to explore the mechanisms underlying this effect. This study aimed to investigate the possible mechanism underlying the inhibitory effect of BMSCs on cardiomyocyte hypertrophy. We induced cardiomyocyte hypertrophy in cultured rat cells through isoproterenol (ISO) treatment with or without BMSC coculture. A mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Subcellular localization and transcriptional activity of FoxO1 are regulated by post‐translational modifications (e.g. phosphorylation), which inhibit FoxO1 by inducing cytoplasmic localization and proteasomal degradation activity of FoxO1 48 . FoxO1 in the nucleus directly binds to the promoter of the antioxidant stress enzyme and exerts antioxidant effects 49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subcellular localization and transcriptional activity of FoxO1 are regulated by post‐translational modifications (e.g. phosphorylation), which inhibit FoxO1 by inducing cytoplasmic localization and proteasomal degradation activity of FoxO1 48 . FoxO1 in the nucleus directly binds to the promoter of the antioxidant stress enzyme and exerts antioxidant effects 49 .…”
Section: Discussionmentioning
confidence: 99%
“…phosphorylation), which inhibit FoxO1 by inducing cytoplasmic localization and proteasomal degradation activity of FoxO1. 48 FoxO1 in the nucleus directly binds to the promoter of the antioxidant stress enzyme and exerts antioxidant effects. 49 In this study, both cellular and animal experiments showed that parishin intervention group was higher protein level of Klotho and FoxO1 than the control group (Figures 4 and 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a type of pluripotent stem cells, BM-MSCs are capable of multi-differentiation and self-renewal. A number of reports have pointed out that BM-MSCs play a role in many diseases, such as kidney disease (24), osteogenesis induction and bone repair (25), tumors (26), rheumatoid arthritis (27), and heart-related diseases (28). In addition, it has been documented that BM-MSCs play a protective role in DR. Zhao H et al have manifested that BM-MSCs can inhibit the progression of DR by inhibiting oxidative stress and inflammatory pathways (29).…”
Section: Discussionmentioning
confidence: 99%
“…Lu et al [ 40 ] proposed FO1–6nls, a FOXO1-derived peptide inhibitor of CDK1/2-mediated phosphorylation of FOXO1 at serine 249, as a potential therapeutic for the treatment of prostate cancers. AMPK phosphorylates FOXO1 and forms the AMPK/ FOXO1 axis, which is involved in multiple pathological processes, such as liver fibrosis[ 41 ], cardiac hypertrophy[ 42 ], and epithelial-mesenchymal transition (EMT)[ 43 ]. The phosphorylation of FOXO3 at serine 644 by IκK normally leads to ubiquitin-dependent proteasomal degradation[ 44 ], but causes cytoplasmic retention in acute myeloid leukemia[ 45 ].…”
Section: Characteristics Of Foxo Family Membersmentioning
confidence: 99%